Tendon Sheath Fibroma (FTS) arising from foot - Anirudh Bansal; Vikramjit Singh; Kailash Sethi; Ajay Mandloi (Journal of Integrated Health Sciences)
Introduction: Tendon Sheath Fibroma (FTS) is a benign but rare condition. Tumor arises from the sheath of the tendon. Case report: Middle aged female having mildly painful swelling on the dorsum of right foot with clinical and histopathological diagnosis of FTS is presented here. Discussion: It is mostly found in the palm and on right side. FTS of foot region is rare. Conclusion: Patient can be successfully treated with surgical excision.